CLINICO-MYCOLOGICAL PROFILE OF DERMATOPHYTIC INFECTIONS - G.KUMARAN AND M.JEYA, (International Journal of Pharma and Bio Sciences, 2014)
The common cause of skin infections are dermatophytes and opportunistic fungi. The prevalence of dermatophyte infection varies with different geographic area and climatic conditions. This study was undertaken to study the clinical pattern and the etiological agents of dermatophyte infections. Clinical samples from 100 patients were subjected to microscopic examination and culture on various media. In total 100 specimens collected, 54 were skin scrapings, 39 were hair samples and 7 were nail clippings. Direct microscopy revealed fungal elements in 65% of the cases, of these 50(77%) were culture positive and 15(23%) was culture negative. No fungal elements were observed in KOH mount in 35% of the cases, of these 5 (14%) yielded growth of fungi and 30(86%) were culture negative. Among the 55 fungal isolates, 49 were dermatophytes.The predominant isolate from all samples were Trichophyton mentagrophytes (33%). The study signifies the importance of mycological examination in the diagnosis of various mycoses for their effective management.